So am struggling to solve this problem as it has been a while since I have been this enticed with mathematics and hence is a bit weary of the subject.

It involves using the factor and remainder theorem to find two constants (a and b) when: $$\ f(x) = x^3 + ax + b$$

and you are given the fact that $(x + 1)$ is a factor of $f(x)$ and you also know that when: $$\frac {f(x)} {(x - 3)}$$ The remainder is 16.

Initially i decided to use the remainder theorem to see if i could work out $a$ and $b$: $$\ f(3) = 3^3 + a(3) + b = 27 + 3a + b$$

but I ended up getting some unfamiliar equation which I didn't think was right.

I'd appreciate it if someone could inform me of how I should ideally try and approach this question as right now am a bit stuck in the mud.


Your way is fine, and is the standard way to approach the problem. After getting $$f(3)=27+3a+b=16 \iff 3a+b=-11$$ Use the factor theorem to get that $$f(-1)=-1-a+b=0 \iff b=a+1$$ Putting this back into our original equation, we get $$4a+1=-11 \iff a=-3$$ And thus $a=-3, b=a+1=-2$. Thus $$f(x)=x^3-3x-2$$ Done.

  • $\begingroup$ Oh yes i see now, thank you very much Sheen! $\endgroup$ – Zochonis Mar 1 '17 at 9:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.